Color confinement and dual superconductivity of the vacuum. I - Biagio Lucini (Physical Review D, 1999)
We study dual superconductivity of the ground state of SU(2) gauge theory, in connection with confinement. We do that measuring on the lattice a disorder parameter describing condensation of monopoles. Confinement appears as a transition to dual superconductor, independent of the abelian projection defining monopoles. Some speculations are made on the existence of a more appropriate disorder parameter. A similar study for SU(3) is presented in a companion paper.